Peculiarities of scintillation materials based on ZnS—ZnTe solid solutions - Katrunov, K.; Lalaiants, O.; Baumer, V.; Galkin, S.; Galchinetskii, L.; Brilyova, Ye. (Functional Materials, 2013)
The optimal conditions for obtaining and features of solid solution ZnS—ZnTe were defined taking into account the thermodynamic calculation of possible chemical reactions in ZnS—ZnTe—H₂—S in a wide temperature range (600—1400 K). It is shown that control of optical, scintillation and crystallographic characteristics of such materials can be performed by co-doping of rare earth elements and adding the nonstoichiometric sulfur in the initial mixture (improvement of the kinetic parameters), as well as by heat treatment in inert atmosphere (Ar ) resulted in phase change of the crystal lattice, increasing the light output, and reducing the afterglow. The reasons of these changes are discussed.